2015
DOI: 10.1111/1752-1688.12300
|View full text |Cite
|
Sign up to set email alerts
|

Considering Climate Change in the Estimation of Long‐Term Flood Risks of Devils Lake in North Dakota

Abstract: Terminal lakes are impacted by regional changes in climate. Devils Lake (DL), North Dakota, United States (U.S.), is a case in which a prolonged shift in the precipitation pattern resulted in a 10-m waterlevel rise over the past two decades, which cost over one billion U.S. dollars in mitigation. Currently, DL is 1.5 m from an uncontrolled overspill to the nearby Sheyenne River, which could lead to unprecedented environmental, social, and economic costs. Water outlets recently implemented in the lake to slow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The results showed that operating two emergency outlets in the past few years has lowered the lake water level by ~0.7 m, but not sufficiently to prevent the lake water level from rising (Figure ). Similar results have been reported in the past (Vecchia, ; Kharel and Kirilenko, ). As there is a ~37% chance for the current wet condition to continue until 2040 (Vecchia, ), these results indicate that Devils Lake will likely reach the natural spill elevation by that time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that operating two emergency outlets in the past few years has lowered the lake water level by ~0.7 m, but not sufficiently to prevent the lake water level from rising (Figure ). Similar results have been reported in the past (Vecchia, ; Kharel and Kirilenko, ). As there is a ~37% chance for the current wet condition to continue until 2040 (Vecchia, ), these results indicate that Devils Lake will likely reach the natural spill elevation by that time.…”
Section: Discussionsupporting
confidence: 92%
“…He found that the emergency outlet operation would significantly decrease, but not completely eliminate, the chance of natural spilling. Using the Soil and Water Assessment Tool (SWAT) with an ensemble of projections from 15 General Circulation Models (GCMs), Kharel and Kirilenko (2015) found a significant probability (7.3 to 20.0%) of overspill in the next few decades in the absence of outlets. None of these studies, however, have tried to examine water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Spring floods in the RRNB are typically associated with cold climate conditions in winter and early spring such as harsh blizzards, early snow‐melting events, and/or ice jam processes in the rivers (Todhunter ). SWAT is a watershed‐scale hydrological and water quality model that is not yet fully capable of simulating the complex snowmelt processes under such a harsh continental climate condition in the RRNB (Wang and Melesse ; Wang et al ; Kharel and Kirilenko ). However, it should be noted that the underestimated peak discharges by the SWAT model did not affect the results of this study because: (1) the outlets were not operational during the historical flooding events when the simulated discharge was significantly underestimated (Figures and ), and (2) the SWAT model performed well in capturing the peak discharges within the range of two‐year flood or the maximum impact of the current outlet operation (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The amplification effect evident in endorheic watersheds makes them important for detection of regional changes in climate, because even relatively small changes in local temperature and precipitation extended over years leads to highly visible changes in water level and lake area, imposing a direct impact on the livelihood of lake-dependent populations. Kharel & Kirilenko (2015) provided numerous examples of closed lakes across the globe with receding (e.g., Aral Sea, Lake Chad, and Qinghai Lake) or rising (e.g., Caspian Sea and Mar Chiquita) waters related to changing climate and land use (see also Rosenzweig et al, 2007 ). While endorheic lakes most commonly experience receding water level due to human activities, DL, located in a sparsely populated Northern Great Plains area close to the US—Canada border (United States Geological Survey (USGS) Souris-Red-Rainy drainage region, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies however did not consider the impacts of global climate change on regional hydrology. Climate change impacts on DL’s flooding were taken into account by Kharel & Kirilenko (2015) , who estimated the probability of future DL levels and associated uncertainty by employing an ensemble of climate change projections used in the 2007 report of the IPCC ( Solomon et al, 2007 ). Further, Kharel, Zheng & Kirilenko (2016) estimated the role of land use change within the DL watershed in the observed flooding.…”
Section: Introductionmentioning
confidence: 99%